Determination of Amino Acid Composition of Two Carp Species by GC-MS - Iordache, A.; Horj, E.; Toma, A.; Cozar, O.; Culea, M. (Asian Journal of Chemistry, 2011)
An isotopic dilution gas chromatography-mass spectrometric (ID-GC/MS) technique was used to evaluate the effects in quantitative amino acids of fish plasma after Se addition in food in comparison with control. The stable isotope internal standard used was 15N-methionine. A trace DSQ ThermoFinnigan quadrupole mass spectrometer coupled with a trace gas chromatography was used. Amino acids were separated on a Rtx-5MS capillary column, 30 m × 0.25 mm, 0.25 μm film thickness, using a temperature program from 50 ºC, 1 min, 6 ºC/min at 100 ºC, 4 ºC/min at 200 ºC, 20 ºC/min at 300 ºC, (3 min). The transfer line temperature was 250 ºC, the injector temperature 200 ºC and ion source temperature 250 ºC; splitter: 10:1. The amino acids were purified on a Dowex 50W-W8 exchange resin and derivatized in a procedure following two steps to obtain trifluoroacetyl butyl esters. Concentrations of majority of free amino acids as methionine, glutamic acid, aspartic acid, lysine, phenylalanine, increased with Se supplementation.